Troublesome Issues in Shrimp Farming Sector of Greater Khulna Region, Bangladesh - Kabiraj, Manash; Khandoker, Shety; Banu, Ghausiatur Reza; Sultana, Shamima (Chittagong University Journal of Biological Sciences, 2024)
The objective of this research was to look for the existent troublesome issues in shrimp farming sector in Khulna, Bagerhat and Sathkhira district of Bangladesh. A total of ninety shrimp farms were visited to collect primary data through questionnaire interview from August-December, 2017. The result showed that, at least fourteen major problems were existing in this sector at present which must be addressed for improving quality shrimp production. Among the major problems identified, disease was the main restraining factor for the development of shrimp farms. Our observations clearly indicated that about 80%, 90% and 80% farms of Khulna, Satkhira and Bagerhat district, respectively suffered from several viral diseases in which WSSV was the most prominent one. Neither of the farmers were found applying appropriate technique to diagnose actual diseases nor even testing any water quality parameter. The farmers were also lacking good quality post larvae, feed, technical knowledge and government patronization. The remaining problems were land ownership and conflict, leasing duration matter, poor economic condition, high credit loan, poor transportation facilities, insufficient electricity supply, natural calamities, poor post- harvest handling facilities, low product price, and inconsistency in market channel were also existed in this region. The Chittagong Univ. J. B. Sci. 9(1&2):141-152,2019